The development of a framework for improvement of intensive care delivery: a systemic intervention - Scribante, Juanett (My University, 2018)
Intensive care is a small but complex system; context-specific and continually confronted by dynamic changes and challenges in the environment. Initiatives following the traditional reductionist approach to improve the delivery of intensive care has had limited success. The aim of this research was to develop a systemic framework for the improvement of intensive care delivery. The factors affecting the delivery of intensive care – in South Africa and internationally – were elucidated by a comprehensive review and analysis of intensive care literature. A further understanding of intensive care delivery in South Africa was obtained by “making sense of the mess” using a systems approach. Systemic intervention served as the meta-methodology and methods and techniques from interactive planning, critical systems heuristics, soft systems methodology and the viable system model were employed. Making sense of the mess emphasised the complexity of intensive care delivery, on both a situational and a cognitive level. It became clear that a single methodology would not suffice, but that a pluralist methodology was required to guide improvement in intensive care delivery. Based on this understanding, nine principles were formulated to guide the development of a framework for the improvement of intensive care delivery. Systemic intervention was used as the meta-methodology. Interactive planning was identified as the key methodology, incorporating methods and techniques from critical systems heuristics, soft system methodology and the viable system model to build a systemic framework for the improvement of intensive care delivery. Embedded in the proposed framework are matters relating to systemicity, complexity, flexibility, empowerment, and transformation of intensive care delivery. The proposed framework allows for multiple-perspectives, including that of marginalised stakeholders, the mitigation of multi-vested interests and power relationships. It is both flexible and adaptable to promote learning about the complex problems of intensive care delivery and it accommodates the strengths of various relevant approaches to complex problem solving. The proposed framework aims to facilitate sustainable improvement of intensive care delivery and to ensure the “just-use” of resources to foster distributive justice. It acknowledges the trajectory of intensive care delivery – the patient comes from the community and returns to the community and intensive care delivery functions on a continuum that ranges from basic to highly sophisticated.
A thesis submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy. September 2018
Keywords: Emergency nursing; Critical care medicine; Nursing--Research